2000
DOI: 10.1021/jp0014364
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Structural and Electronic Properties of a Real Size MoS2 Slab:  Mo27S54

Abstract: It is shown that ab initio MO approaches are suitable to simulate the relatively large hexagonal MoS 2 slab corresponding to the average initial size (15-20 Å) of MoS 2 on alumina-supported catalysts used in hydrodesulfurization (HDS) and hydrogenation (HYD) of petroleum fractions. By using a general ab initio MO program, GAMESS, the structure optimization of the Mo 27 S 54 slab is possible at the UHF/MINI/ECP)SBK level of theory, providing helpful information on the structural and electronic properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…Compared to the other cases, reactions (3) and (7) show high positive enthalpy (14.7 and 41.5 kcal/mol), indicating that this type of sulfur vacancy is relatively difficult to form. The negative enthapies of reactions (2), (4), (6), (8) and (10) show that formations of corresponding reduced structure are thermodynamically favorable for atomic hydrogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the other cases, reactions (3) and (7) show high positive enthalpy (14.7 and 41.5 kcal/mol), indicating that this type of sulfur vacancy is relatively difficult to form. The negative enthapies of reactions (2), (4), (6), (8) and (10) show that formations of corresponding reduced structure are thermodynamically favorable for atomic hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown experimentally that the removal of S atoms from a MoS 2 slab starts from the edge on which the formed CUS has strong adsorption affinity for thiophene and H 2 S and is responsible for the thiophene HDS [5,6]. Although it is easy to form 2-fold CUS on the (1 0 1 0) edge of MoS 2 even under the atmosphere of H 2 , the 2-fold CUSs may not activate the thiophene to the degree of cleaving S C bond of thiophene [7,8]. More specifically, 3-and 4-fold CUSs formed at the edge of (1 0 1 0) together with SH groups seem to be responsible for the activation of HDS [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the reaction of H 2 with MoS 2 clusters was endothermic. Analyzing a bigger cluster, Mo 27 S 54 [58], the authors concluded that there are two types of twofold unsaturated sites (CUS): those on the corners are potentially active sites for HDS reactions while the others on the (1010) edges are only reactive to -bond activation.…”
Section: Ab Initio Methods In Catalysismentioning
confidence: 99%
“…There are in the literature several works on MoS 2 clusters using a variety of cluster sizes, with methods ranging from semiempirical 17,[41][42][43][44][45][46] to ab initio and DFT. 3,18,30,[47][48][49][50][51][52][53][54] In particular, the investigation of Wen et al 52 concentrated in the study of structure and stability of MoS x clusters with the change of sulfur coverage on both Mo and S edges and the effect of cluster sizes on the surface structures from a thermodynamic point of view.…”
Section: Introductionmentioning
confidence: 99%